Perbedaan Antara Model Flipped Classroom Dengan Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Pada Pembelajaran Ips Materi Keragaman Budaya - Salsabila, Annisa Anastasia; Rustini, Tin; Kusnadi, Uus (Universitas Hamzanwadi, 2025)
Social Studies (IPS) education at the elementary level aims to foster critical thinking and problem-solving skills, yet traditional teaching methods often fall short in achieving these goals. This study compares the effectiveness of the Flipped Classroom and Problem-Based Learning (PBL) models in enhancing students’ problem-solving competencies, particularly in the context of cultural diversity. A quasi-experimental design, specifically the Nonequivalent Control Group Design, was employed, involving 4th-grade students divided into two groups: one taught via Flipped Classroom (using Google Sites for home-based learning) and the other via PBL. Data were collected through pre-tests and post-tests and analyzed using Independent Sample t-test in SPSS.Results indicated that both methods improved problem-solving skills, with post-test averages rising from 47.2 to 85.6 (Flipped Classroom) and 46.6 to 76.2 (PBL). Statistical analysis revealed a significant difference between the groups (p = 0.003 < 0.05), confirming the superiority of Flipped Classroom. The model’s flexibility in self-paced learning and structured in-class discussions enabled deeper engagement and collaboration, aligning with 21st- century educational demands. This study underscores the potential of Flipped Classroom as an innovative approach to cultivating problem-solving skills in culturally diverse settings. Educators are encouraged to integrate technology and student-centered strategies to create adaptive learning environments